Masi: A mechanical ventilator based on a manual resuscitator with telemedicine capabilities for patients with ARDS during the COVID-19 crisis - Chang, J.; Acosta, A.; Benavides-Aspiazu, J.; Reategui, J.; Rojas, C.; Cook, J.; Nole, R.; Giampietri, L.; Pérez-Buitrago, S.; Casado, F.L.; Castañeda, B. (Elsevier, 2021)
In this article, we introduce a portable and low-cost ventilator that could be rapidly manufactured, to meet the increasing demand of ventilators worldwide produced by COVID-19 pandemic. These ventilators should be rapidly deployable and with functional capabilities to manage COVID-19 patients with severe acute respiratory distress syndrome (ARDS). Our implementation offers robustness, safety and functionality absent in existing solutions to the ventilator shortage (i.e., telemonitoring, easy-to-disinfect, modularity) by maintaining simplicity. The design makes use of a manual resuscitator as the core respiration component activated by a compression mechanism which consist of two electronically controlled paddles. The quality measurements obtained after testing on a calibrated artificial lung demonstrate repeatability and accuracy exceeding human capabilities of manual ventilation. The complete design files are provided in the supplementary materials to facilitate ventilator production even in resource-limited settings. The implementation of this mechanical ventilator could eliminate device rationing or splitting to serve multiple patients on ICUs.
Keywords: Acute respiratory distress syndrome; COVID-19 pandemic; Critical care; Mechanical ventilation; Respiratory insufficiency; https://purl.org/pe-repo/ocde/ford#3.02.07